Constructions of Moral Values in Reader Comments of the Samantha Sex Robot Discourse in East African Newspapers - Njuguna, Joseph (Journal of religion, media and digital culture, 2021)
Abstract Although artificial intelligence (ai) has been touted as revolutionary, this technology has sparked ethical concerns, with man accused of attempting to create a ‘play God’ with it. While creators of sex robots have been hailed for reigniting sexual relationships, they have received flack in equal measure for their apparent moral absurdity. From a Christian values perspective, this study interrogates how the Samantha sex robot invention was framed in 129 online reader comments in two East African newspapers – The Standard and The Daily Monitor. Findings showed that comments fell under the value themes of ‘family bond’, ‘compromised conscience’, and ‘apocalypse’. While a few positioned sex robots as a panacea to domestic instability, the majority opinion viewed the robots as ‘destroyers’ of the God-ordained family unit and tools of dehumanizing women, and thus morally contradictory to Christian teachings. Justifying sex robots was considered to be ‘negotiating’ or ‘rationalizing’ with established Christian values and therefore ‘rebelling against God’. Man’s extremity with the creation and use of sex robots sparked predictions of a self-fulfilling prophecy of his extermination for inciting the wrath of God. The preservation of culture also underpinned the ethical evaluations of robots by some commenters.